PENGARUH PENAMBAHAN ABU SEKAM PADI TERHADAP KUAT TEKAN MORTAR - Pascasari, Auliarizky; Wahyuni, Ade Sri; Islam, Mukhlis; Gunawan, Agustin; Afrizal, Yuzuar (Inersia: Jurnal Teknik Sipil, 2021)
The purpose of this research is to know the comparison of compressive strength mortar with additional material rice husk ash to normal mortar. Rice husk ash used has been burned at high temperatures above 400°C. The percentages of rice husk ash used are 6%, 9%, 12%, and 15% with 7 samples in each variations. The total of mortar cubes are 105 pieces sized 50mm x 50mm x 50mm. The range of initial flow values are used 105%-115% (SNI 03-6882-2002). The test specimen was immersed for 13, 20, and 27 days and mortar compressive strength test was conducted at the age of 14, 21, and 28 days. The highest compressive strength occurred at 9% variation with an average compressive strength value of 13,24 MPa, with a percentage increase of 10,15% from normal mortar. The lowest compressive strength occurred at 6% variation with an average compressive strength value of 11,22 MPa, with percentage decrease of 6,66% from normal mortar. The result shows that the use of rice husk ash with variation 9% and 12% produce higher compressive strength than normal mortar.